Quantification of the Dynamic Interface Evolution in High‐Efficiency Working Li‐Metal Batteries - Ding, Jun‐Fan; Xu, Rui; Ma, Xia‐Xia; Xiao, Ye; Yao, Yu‐Xing; Yan, Chong; Huang, Jia‐Qi (Angewandte Chemie International Edition, 2022)
Lithium (Li) metal has been considered a promising anode for next‐generation high‐energy‐density batteries. However, the low reversibility and intricate Li loss hinder the widespread implementation of Li metal batteries. Herein, we quantitatively differentiate the dynamic evolution of inactive Li, and decipher the fundamental interplay among dynamic Li loss, electrolyte chemistry, and the structure of the solid electrolyte interphase (SEI). The actual dominant form in inactive Li loss is practically determined by the relative growth rates of dead Li0 and SEI Li+ because of the persistent evolution of the Li metal interface during cycling. Distinct inactive Li evolution scenarios are disclosed by ingeniously tuning the inorganic anion‐derived SEI chemistry with a low amount of film‐forming additive. An optimal polymeric film enabler of 1,3‐dioxolane is demonstrated to derive a highly uniform multilayer SEI and decreased SEI Li+/dead Li0 growth rates, thus achieving enhanced Li cycling reversibility. The fundamental interplay among Li dynamic loss behavior, electrolyte composition, and the structure of the solid electrolyte interphase (SEI) layer was quantitatively elucidated. The actual dominant form in inactive Li loss is determined by the relative growth rates of dead Li0 and SEI Li+ as the anode interface undergoes processive evolution during cycling. The mechanistic studies shed fresh light on the interfacial dynamics of the Li‐metal anode.